Skrining Fitokimia Daun Delima (Punica Granatum L.) - Chusnul Mar'iyah Mahmud; Nadila Nadila; Muhammad Jalaluding; Kristina Tresia Leto (International Forum of Researchers and Lecturers, 2025)
Pomegranate (Punica granatum L.) is a fruit plant that is easy to grow in almost all climates. The utilization of this plant as a traditional medicine is very varied and all parts of the pomegranate plant (Punica granatum L.) can be used as medicine, one of which is pomegranate leaves. This study aims to determine the content contained in pomegranate leaves. Pomegranate leaves were extracted by maceration with 96% ethanol solvent. The extraction results then go through a color reaction compound test process. Testing of color reaction compounds includes saponins, steroids/terpenoids, flavonoids, alkaloids, and tannins. This study aims to analyze the content of chemical compounds contained in pomegranate leaves extracted using 96% ethanol. This research method includes maceration extraction and chemical compound screening tests using chemical reagents. The results showed that pomegranate leaves extracted using 96% ethanol solvent and phytochemical screening showed positive results on alkaloid compounds, steroids/terpenoids, flavanoids, tannins but on saponin metabolites showed negative results.